The Post-Seven-Day Tahlilan Tradition: Living Hadith as a “Reminder of Death” in Tegal Sari Village, Serang, Banten - Muhammad Yushron Kurniawan; Muhammad Alif (Sufiya Journal of Islamic Studies, 2025)
This study examines the phenomenon of Living Hadith in the tradition of religious gatherings (tahlilan) held on Thursday nights seven days after a death in Tegal Sari Village, Walantaka District, Serang City, Banten. Employing a descriptive qualitative method with the Living Hadith approach developed by Saifuddin Zuhri Qudsy, data were collected through participatory observation and in-depth interviews with religious leaders and community members. The findings reveal that the tradition of Thursday night religious gatherings seven days after a death represents a concrete manifestation of Living Hadith in the socio-religious practices of the community, even though hadith values are not always referenced textually. The primary values actualized include silaturahmi (social bonds with kin, as in Sahih Bukhari no. 1925), remembrance of death (as in Sahih Tirmidzi no. 2307), social empathy, mutual cooperation (gotong royong), charity (sedekah), and da'wah through religious exhortations (tausiyah). This tradition deserves preservation as it aligns with hadith exhortations to strengthen silaturahmi, foster empathy and mutual assistance among fellow Muslims, and refresh awareness of human mortality. These findings affirm that Living Hadith in the seven-day post-death tahlilan tradition serves as an effective medium for da'wah actualization, simultaneously reinforcing social solidarity and faith within the Muslim community.